2010
DOI: 10.2113/jeeg15.1.29
|View full text |Cite
|
Sign up to set email alerts
|

2-D Electrical Resistivity Imaging to Assess Slurry Pond Subsoil Pollution in the Southeastern Region of Murcia, Spain

Abstract: About 2,341 pig farms generate large amounts of slurry in the southeastern Region of Murcia, Spain. Given the nature of the pig slurry as well as its amount produced in livestock, it has become a matter of growing environmental concern. The control of slurry ponds is now a top priority concern to create a safer environment, especially for agricultural production. This study reports the results of a much wider and comprehensive project carried out to collect reliable data on the behavior of slurry, soil, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Figure 6 shows the lithological columns obtained from drilling operations in the three slurry ponds corresponding to Quaternary deposits [21]. These lithological results (from BH1, BH2, and BH3 borehole) are in line with those presented by Martínez-Pagán et al (2010) [36], who identified the presence of caliche horizons alternating with layers of gravel and clay. BH1 borehole, which corresponds to slurry pond No.…”
Section: Borehole Samples and Physicochemical Analysessupporting
confidence: 74%
“…Figure 6 shows the lithological columns obtained from drilling operations in the three slurry ponds corresponding to Quaternary deposits [21]. These lithological results (from BH1, BH2, and BH3 borehole) are in line with those presented by Martínez-Pagán et al (2010) [36], who identified the presence of caliche horizons alternating with layers of gravel and clay. BH1 borehole, which corresponds to slurry pond No.…”
Section: Borehole Samples and Physicochemical Analysessupporting
confidence: 74%
“…This method is mainly used for detecting some fissures or holes in the underground layer in relation to the geological structures [10]. The application of ER extended to the environmental pollution investigations, such as investigating the pipeline leak incidents, verify the sewage leakage, and detect the soil contamination [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover advances in inversion software and computer technology have enabled better modelling of resistivity data. Common uses of ERT include water exploration and contaminant flow detection (Bensom et al, 1997;de Lima et al, 1995;Martínez-Pagán et al, 2010), in engineering site investigations (Banham and Pringle, 2011;Rucker et al, 2009) locating buried artefacts or structures in Archaeological surveys (Negri et al, 2008;Tonkov and Loke, 2006) as well as providing geological and hydrogeological site information (Essahlaoui et al, 2001;Ganerod et al, 2006).…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%